2019
DOI: 10.22201/ib.20078706e.2019.90.2780
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oribatid mites from agricultural soils with contrasting irrigation types in Hidalgo State, Mexico: a case study

Abstract: The objective of this work is to know the structure (composition and density) of the community of the oribatid mites and their relationship to edaphic parameters in 2 agricultural parcels with different type of irrigation. It constitutes the first work done with oribatid mites in agricultural plots irrigated with waste water in Mexico. Two agricultural parcels were selected: one is irrigated with waste water (San Salvador) and the other with well water (El Bondho) from the municipality of San Salvador. The den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…The presence of several plants also increases the number of Oribatida species, even when the concentration of heavy metals is high in the soil (Manu et al, 2019). Iglesias et al (2019) studied the effects of heavy metals on abundance and community structure in irrigated agricultural fields in Mexico (19°40' -20°29' N; 99°57' -99°27' W Mezquital Valley, Hidalgo). The study area is irrigated with wastewater, which has high concentrations of heavy metals that accumulate in the soil over time.…”
Section: Ecological Indicationmentioning
confidence: 99%
“…The presence of several plants also increases the number of Oribatida species, even when the concentration of heavy metals is high in the soil (Manu et al, 2019). Iglesias et al (2019) studied the effects of heavy metals on abundance and community structure in irrigated agricultural fields in Mexico (19°40' -20°29' N; 99°57' -99°27' W Mezquital Valley, Hidalgo). The study area is irrigated with wastewater, which has high concentrations of heavy metals that accumulate in the soil over time.…”
Section: Ecological Indicationmentioning
confidence: 99%
“…Hammer (1962) recorded it from Chile near the coast of Puerto Montt. Ojeda (1989) and Iglesias et al (2019) reported it from Mexico, in Hidalgo and Mexico states. (Hammer, 1961) Observations: costula, crista and seta in absent; notogastral setae not dilated distally, sensillus slightly dilated and bilaterally ciliated.…”
Section: Oppiidae: Oppioideamentioning
confidence: 99%
“…Kamel (2020), evaluó el efecto del acetoclor en la población de ácaros oribátidos en el suelo y determinó que este compuesto juega un papel importante en la disminución de la actividad de estos organismos. Los cuales según Iglesias & Palacios-Vargas, José G Castaño-Meneses (2019) , estos ácaros juegan un papel ecológico importante y actúan como indicadores de perturbación del medio.…”
unclassified